Neural substrates of shared visual experiences: a hyperscanning fMRI study. Issue 12 (28th June 2021) - Yoshioka, Ayumi; Tanabe, Hiroki C; Sumiya, Motofumi; Nakagawa, Eri; Okazaki, Shuntaro; Koike, Takahiko; Sadato, Norihiro
Abstract: Sharing experience is a fundamental human social cognition. Since visual experience is a mental state directed toward the world, we hypothesized that sharing visual experience is mediated by joint attention (JA) for sharing directedness and mentalizing for mental state inferences. We conducted a hyperscanning functional magnetic resonance imaging with 44 healthy adult volunteers to test this hypothesis. We employed spoken-language-cued spatial and feature-based JA tasks. The initiator attracts the partner's attention by a verbal command to a spatial location or an object feature to which the responder directs their attention. Pair-specific inter-individual neural synchronization of task-specific activities was found in the right anterior insular cortex (AIC)–inferior frontal gyrus (IFG) complex, the core node of JA and salience network, and the right posterior superior temporal sulcus, which represents the shared categories of the target. The right AIC-IFG also showed inter-individual synchronization of the residual time-series data, along with the right temporoparietal junction and dorsomedial prefrontal cortex—the core components for mentalization and the default mode network (DMN). This background synchronization represents sharing the belief of sharing the situation. Thus, shared visual experiences are represented by coherent coordination between the DMN and salience network linked through the right AIC-IFG.